Impulse Buying Behavior: The Impact Of Store Atmosphere, Promotions, And Hedonic Shopping Motivations - Batisuta, Jeremy Gabriel; Hapsari, Raditha Dwi Vata (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Impulse buying behavior has become increasingly relevant in modern retail, especially in the fashion sector, where visual and emotional cues strongly influence consumer decisions. This study aims to analyze the influence of visual merchandising, sales promotion, and hedonic shopping motivation on impulse buying behavior. A quantitative descriptive approach was applied. The population in this study includes all consumers of H&M stores. The sampling technique used is non-probability sampling with a purposive sampling method. This research examines four variables: hedonic shopping motivation, promotion, visual merchandising, and impulse buying. According to the guidelines proposed by Roscoe (1975) in Sekaran & Bougie (2020), the minimum sample size is 10 times the number of variables (10 × 4 = 40 respondents). However, to enhance population representation, the sample size was increased to 160 respondents (based on 10 × 16 indicators = 160). Data were analyzed using multiple linear regression with SPSS software. The results show that visual merchandising has a significant positive effect on impulse buying behavior. In contrast, promotion and hedonic motivation show weaker influences. The novelty of this study lies in integrating emotional, promotional, and visual factors into a single analytical framework. The implication suggests that retailers should prioritize visual strategies to stimulate unplanned purchasing behavior.